Le mausolée de la villa d’Ussol à Saint-Rémy-de-Provence (Bouches-du-Rhône) - Philippe Mellinand; Elsa Sagetat-Basseuil (Gallia)
The mausoleum excavated at the Ussol ZAC (Saint-Rémy-de-Provence, Bouches-du-Rhône) presents distinctive features that make it all the more interesting: funerary chamber in a large structure, dating going back to the Late Roman Empire, located just beside a villa... It was originally built for a single, central burial, but seems to have been partly rebuilt to accommodate a second stone vault, next to the first one, in the semi-hypogeum chamber. This reconstruction, while the chamber was still in use, was followed by the widespread spoliation of the monument at the end of Antiquity. Thus, only a few architectural elements corresponding to the elevation of the mausoleum have been preserved. Nevertheless, based on the observation of reused blocks discovered in the villa, and thanks to the few elements of preserved decoration, it is possible to reproduce a mausoleum-temple type building.